Muhammadiyah Through the Ages: From Reformist Ideas to a Civilizational Movement - Marlina Gazali; Muh. Syahrul Mubarak; Rosmini Rosmini; Ghufran Al Ghifary Kamiluddin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to analyze the founding ideas of Muhammadiyah, its organizational dynamics, and the periodization of its development from 1912 to the contemporary era, with particular attention to the movement’s educational orientation as a core instrument of social transformation. This research adopts a historical-sociological approach by examining primary and secondary sources relevant to Muhammadiyah’s intellectual roots, institutional practices, and socio-religious engagement. The findings indicate that the establishment of Muhammadiyah was driven by three major factors: colonial conditions that contributed to Muslim socio-educational marginalization, the persistence of syncretic religious practices within local communities, and the influence of Islamic reformist currents from the Middle East. Over time, Muhammadiyah has maintained ideological consistency in the spirit of tajdid through religious purification and the modernization of social services, particularly in the development of schools, universities, and community-based educational programs. Organizationally, Muhammadiyah demonstrates strong adaptive capacity in responding to political and social changes from the colonial era through independence, the New Order, and the reform and globalization periods. Its historical periodization shows that Muhammadiyah functions not only as a da’wah movement but also as a strategic actor in strengthening civil society, cultivating educated citizenship, and expanding international humanitarian diplomacy. Therefore, Muhammadiyah can be understood as a model of progressive Islamic movement that integrates religious orthodoxy with modern educational and social praxis within both national and global contexts.